ADOLESCENT'S PERSONAL BRANDING ON INSTAGRAM - Etty Susilowati Achmad; Lisnawati Ruhaena (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2021)
Personal branding is an individual effort to obtain the response and perception of public audiences through social media, including Instagram. This study aimed to describe adolescents' experiences in personal branding through Instagram and the meaning of personal branding. It is qualitative research with a descriptive phenomenological approach. Data were analyzed using thematic phenomenological analysis techniques to understand the themes and patterns of personal branding. Data were collected using interviews and observation methods. Five participants were obtained through purposive sampling technique with criteria: adolescents aged 18-21 years and active Instagram users (with a consistent content theme). Results show that the personal branding process is built through stages that involve determining goals, conceptualizing content, and posting content. It is essential to concept and edit content uniquely and posts consistently at the right time and the right frequency, including the highlight menu setting. Personal branding has significant and strategic meanings for adolescents: as a medium to promote competencies, expand career opportunities, and be a useful person. Essentially, it is recommended for adolescents to do personal branding as an alternative activity that supports self-development and careers using Instagram.